2009
DOI: 10.1002/lary.20537
|View full text |Cite
|
Sign up to set email alerts
|

Comparison among different available surgical approaches in T1 glottic cancer

Abstract: Laser surgery appears to be a very effective management modality for T1 glottic cancer with comparable results to open procedures and a lower incidence of complications. A transcervical approach should be reserved only for selected cases where individual anatomic factors do not permit complete tumor exposure during diagnostic microlaryngoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 29 publications
(53 reference statements)
1
43
0
1
Order By: Relevance
“…Although this resection type is not considered ideal and presents difficulties for histological assessment, studies have demonstrated no sacrifice of oncological control when block-wise resection of the tumour in discrete segments is performed. [9][10][11] It has also been suggested that for a bulky tumour, removing it in sections has the advantage of defining the depth of tumour penetration and delineating the deep margin under high magnification. 12 More than half of our specimens were mounted and orientated for pathological examination and most followed the ENT UK recommendation of using the Glasgow technique of mounting the orientated specimen on dehydrated cucumber.…”
Section: Discussionmentioning
confidence: 99%
“…Although this resection type is not considered ideal and presents difficulties for histological assessment, studies have demonstrated no sacrifice of oncological control when block-wise resection of the tumour in discrete segments is performed. [9][10][11] It has also been suggested that for a bulky tumour, removing it in sections has the advantage of defining the depth of tumour penetration and delineating the deep margin under high magnification. 12 More than half of our specimens were mounted and orientated for pathological examination and most followed the ENT UK recommendation of using the Glasgow technique of mounting the orientated specimen on dehydrated cucumber.…”
Section: Discussionmentioning
confidence: 99%
“…Though radiotherapy is considered the treatment of choice in many European countries, there are a number of recent studies emphasizing the importance of surgery in treatment of early glottic carcinoma [24, 11]. Both surgery and radiotherapy provide good locoregional control and satisfactory functional results, so other factors come into consideration when choosing the adequate treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, recurrent malignancy was noted in 7.7% patients in endoscopic laser cordectomy group and in 9.1% in open cordectomy group. Comparing different surgical approaches, Karatzanis et al had 5-year disease-specific survival of 96.5% for T1a cases and no statistically significant differences noted between different types of procedures: cordectomy and transoral laser microsurgery [11]. Motta et al published survival rate of 85% and adjusted survival rate of 97% in 432 T1aN0 M0 patients treated with transoral laser microsurgery.…”
Section: Discussionmentioning
confidence: 99%
“…Despite advances in the development of conventional therapies such as surgery, radiotherapy and chemotherapy, the 5-year survival rate for patients with LSCC remains unsatisfactory (~50-70%) (2). Locoregional recurrences, lymph node and distant metastasis are major causes of death that significantly affect prognosis in LSCC patients (3).…”
Section: Introductionmentioning
confidence: 99%